Monoclonal antibodies for use in detection of Bacillus and Clostridium spores. - Quinlan, J J (1997)
Five monoclonal antibodies against bacterial spores of Bacillus cereus T and Clostridium sporogenes PA3679 were developed. Two antibodies (B48 and B183) were selected for their reactivity with B. cereus T spores, two (C33 and C225) were selected for their reactivity with C. sporogenes spores, and one (D89) was selected for its reactivity with both B. cereus and C sporogenes spores. The isotypes of the antibodies were determined to be immunoglobulin G2a (IgG2a) (B48), IgG1 (B183), and IgM (C33, C225, and D89). The antibodies reacted with spores of B. cereus T, Bacillus subtilis subsp. globigii, Bacillus megaterium, Bacillus stearothermophilus, C. sporogenes, Clostridium perfringens, and Desulfotomaculum nigrificans. Antibody D89 also reacted with vegetative cells of B. cereus and C. sporogenes. Analysis of B. cereus spore extracts showed that two of the antigens with which the anti-Bacillus antibodies reacted had molecular masses of 76 kDa and approximately 250 kDa. Immunocytochemical localization indicated that antigens with which B48, B183, and D89 react are on the exosporium of the B. cereus T spore. Antibody D89 reacted with the exosporium and outer cortex of C. sporogenes spores in immunocytochemical localization studies but did not react with extracts of C. sporogenes or B. cereus spores in Western blotting. Some C. sporogenes antigens were not stable during long-term storage at -20 degrees C. Antibodies B48, B183, and D89 should prove to be useful tools for developing immunological methods for the detection of bacterial spores.